2010
DOI: 10.12973/ejmste/75245
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Mentoring Practices: A Case Study in Turkey

Abstract: Throughout the world standards have been developed for teaching in particular key learning areas. These standards also present benchmarks that can assist to measure and compare results from one year to the next. There appears to be no benchmarks for mentoring. An instrument devised to measure mentees' perceptions of their mentoring in primary science was administered to 304 preservice teachers in Turkey. Results indicated that the majority of mentees perceived they received mentoring practices, however, 20% or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…There is also a growing body of evidence concerning student teachers PCK (De Jong 2000;De Jong and Van Driel 2004;De Jong, Van Driel, and Verloop 2005;Halim and Meerah 2002;Hudson, Usak and Savran-Gencer 2009;Hudson, Usak, and Savran-Gencer 2010;Usak 2005Usak , 2009Van Driel, Verloop and De Vos 1998;Van Driel, De Jong, and Verloop 2002). These studies have generally concluded that most primary school teachers have various pedagogical misconceptions and often do not have the necessary pedagogical content knowledge to teach science effectively.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…There is also a growing body of evidence concerning student teachers PCK (De Jong 2000;De Jong and Van Driel 2004;De Jong, Van Driel, and Verloop 2005;Halim and Meerah 2002;Hudson, Usak and Savran-Gencer 2009;Hudson, Usak, and Savran-Gencer 2010;Usak 2005Usak , 2009Van Driel, Verloop and De Vos 1998;Van Driel, De Jong, and Verloop 2002). These studies have generally concluded that most primary school teachers have various pedagogical misconceptions and often do not have the necessary pedagogical content knowledge to teach science effectively.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The situation may impact negatively on the mentoring relationship preventing pre-service teachers from developing their teaching competences. Periodic mentoring workshops addressing leadership styles, time and class management, balancing teaching and mentoring responsibilities as well as group work, content and pedagogical knowledge can help support mentor development (Hudson, Uşak & Savran-Gencer, 2010). Recognizing the expertise of peers, acknowledging and compensating their contribution to professional development of their peers can go a long way toward ensuring the development of their pedagogical and professional competencies (Searby, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the mentors are interested in and willing to be a mentor for the teacher students at the School of Vocational Teacher Education. As Hudson, Usak, and Savran-Gencer [15] have stated, the mentors are not especially interested in gaining any financial benefit from their role as mentors; rather, they expect to acquire new ideas and refresh their thinking through the mentoring relationship.…”
Section: Summary Of Challengesmentioning
confidence: 99%